Analisis Kesuksesan Penerapan Sistem Informasi Administrasi Kependudukan Menggunakan Model Delone Dan Mclean - Alex Yuswandi Zalukhu; Joni Yanto Gulo; Nelly Astuti Hasibuan (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The Department.of.Population and Civil Registration (DISDUKCAPIL) of Medan City is one of the agencies that work in the field of community data. The Department of Population and Civil Registration has developed inthe field of technology, namely the application of the Population Administration Information System (SIAK). ThePopulation Administration Information System (SIAK) is one of the application software that plays an importantrole in population data collection, especially in one of the cities in North Sumatra, namely Medan City. Thisapplication is equipped with procedures and is accompanied by special standards according to the rules of thegovernment of the Republic of Indonesia. This research is entitled